Experimental approaches to study plant cell walls during plant-microbe interactions - Xia, Ye; Petti, Carloalberto; Williams, Mark A.; DeBolt, Seth (Frontiers in Plant Science, 2014)
Plant cell walls provide physical strength, regulate the passage of bio-molecules, and act as the first barrier of defense against biotic and abiotic stress. In addition to providing structural integrity, plant cell walls serve an important function in connecting cells to their extracellular environment by sensing and transducing signals to activate cellular responses, such as those that occur during pathogen infection. This mini review will summarize current experimental approaches used to study cell wall functions during plant-pathogen interactions. Focus will be paid to cell imaging, spectroscopic analyses, and metabolic profiling techniques